Phineas Brown papers - Brown, Phineas, 1747-
Daybook kept by Brown recording his business transactions in New Haven, Vt., and later in Vergennes and Waltham. Contains an index as well as genealogical data pertaining to the Phineas Brown family. Includes miscellaneous loose receipts and fragments.
Farmer and storekeeper of Addison County, Vt..
Collection material in English.
Keywords: Brown family; Agriculture -- Vermont -- Addison County; Commerce; General stores -- Vermont -- Addison County; Genealogy; Addison County (Vt.) -- History; New Haven (Vt.) -- History; Vergennes (Vt.) -- History; Vermont -- History; Waltham (Vt.) -- History; Farmers; Merchants